DISTINCTIVE FEATURES OF FUNCTIONAL STYLES OF THE RUSSIAN LANGUAGE AND THEIR APPLICATION - Темирова Шоира Гайбуллаевна; Очилова Насиба Нематовна, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This scientific article discusses the functional styles of the Russian language, their unique features and application in various spheres of life. The importance of using the correct style for successful communication is emphasized.